Development of a copper-substituted, Prussian blue-impregnated, nonwoven cartridge filter to rapidly measure radiocesium concentration in seawater. Issue 9 (1st September 2016) - Yasutaka, Tetsuo; Miyazu, Susumu; Kondo, Yoshihiko; Tsuji, Hideki; Arita, Koichi; Hayashi, Seiji; Takahashi, Akira; Kawamoto, Tohru; Aoyama, Michio
ABSTRACT: This paper presents a cartridge filter incorporating a nonwoven fabric impregnated with Prussian blue copper analog (Cu-CF) to effectively concentrate and quantify radiocesium dissolved in seawater. The recovery ratio of the Cu-CF was >95% in laboratory experiments at a flow rate of 0.5 L min −1 through the filter and >93% in field experiments. Test measurements of 137 Cs concentrations in seawater using Cu-CF agreed with the results obtained by using a conventional coprecipitation method that employed ammonium phosphomolybdate (within the counting error of the detector). The proposed method can shorten the preconcentration and pretreatment times for radiocesium, to just 40 min in 20 L of seawater, which is much faster than the ∼1 week required by traditional ammonium phosphomolybdate methods.